MENYELESAIKAN SOAL CERITA BANGUN RUANG SISI DATAR SISWA MTs BERDASARKAN TAHAPAN NEWMAN - Mar'atus Sholihah; Edy Nurfalah (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2018)
To describe the ability to solve story problems, build a flat-side space using the Newman stage, researchers conducted descriptive research using qualitative and quantitative data. The subjects of this study were all students of class VIII A MTs Musthofawiyah Nguruan in the academic year 2017/2018 consisting of 17 students. Data retrieval was carried out through a description and interview test with descriptive data analysis techniques developed based on indicators of problem solving ability based on Newman stages. The research data shows the ability to solve story problems in building a flat side of class VIII A MTs Musthofawiyah Nguruan in the 2017/2018 school year based on the Newman stage is in less qualification, with the following questions: the ability of students to understand the problem in sufficient qualifications, students' ability to transform the problem in sufficient qualifications, the ability of students in the processing skills stage is lacking.